2022
DOI: 10.1186/s13063-022-06158-3
|View full text |Cite
|
Sign up to set email alerts
|

Minimal effective dose of ultrasound-guided rectus sheath block to reduce oral analgesic requirement after ambulatory laparoscopic tubal resection: a randomized controlled superiority trial

Abstract: Background The effective dose during ultrasound-guided rectus sheath block (URSB) for reducing pain after laparoscopic tubal ligation is reported to be 100 mg of 0.25% bupivacaine. We examined the minimal effective dose of 0.25% bupivacaine for URSB on oral analgesic requirement after ambulatory single-port laparoscopic tubal resection. Methods A prospective, randomized controlled, superiority trial was conducted among patients who had been schedul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Five studies reported 24-h IV morphine equivalent consumption for nine RSB trial comparisons. [ 30 32 34 36 37 40 41 42 ] Overall, RSB was found to provide superior postoperative consumption of analgesics in contrast to controls after 24 h (SMD = -1.55, 95% CI [-2.35, -0.74], P < 0.001). Heterogeneity was considered considerable (I 2 = 95%, Cochrane Q statistic P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies reported 24-h IV morphine equivalent consumption for nine RSB trial comparisons. [ 30 32 34 36 37 40 41 42 ] Overall, RSB was found to provide superior postoperative consumption of analgesics in contrast to controls after 24 h (SMD = -1.55, 95% CI [-2.35, -0.74], P < 0.001). Heterogeneity was considered considerable (I 2 = 95%, Cochrane Q statistic P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…A final total of 20 RCTs satisfied our inclusion criteria and were included in this analysis [ Table 1 ]. [ 5 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 ] The risk-of-bias analysis for all included studies is summarised in Figure 2 . Details on the evidence review for the primary and secondary outcomes can be found in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent RCT showed improved postoperative pain management in an outpatient laparoscopic tubal resection, with the use of bupivacaine in a rectus sheath block (RSB) [141]. Although less is known so far and further investigation is needed to establish the role of a RSB in the outpatient setting.…”
Section: Abdominal Wall Blocksmentioning
confidence: 99%